Epithelioid Angiosarcoma Arising from a Huge Leiomyoma: A Case Report and a Literature Review - Takeya Hara; Ai Miyoshi; Yuji Kamei; Nao Wakui; Akiko Fujishiro; Serika Kanao; Hirokazu Naoi; Hirofumi Otsuka; Takeshi Yokoi (Hindawi Limited, 2018)
Uterine mesenchymal tumors other than leiomyosarcoma, carcinosarcoma, and endometrial stromal sarcomas are extremely uncommon. We describe a case of epithelioid angiosarcoma of the uterus and review previous literature on such rare tumors. A 48-year-old woman presented with a 1-year history of abdominal fullness and 10kg weight loss. Pelvic magnetic resonance imaging (MRI) revealed a huge (30×18cm) uterus accompanied by degeneration and necrosis. She underwent supracervical hysterectomy and right salpingo-oophorectomy. We postoperatively diagnosed the mass as an epithelioid angiosarcoma arising from a leiomyoma. Vasodilatation was observed within the range of 2 cm × several mm in the leiomyoma, and proliferation of atypical cells was observed covering the surface of the luminal side. The tumor showed a partly fine vascular structure and was associated with obvious nuclear atypia and mitotic figures. She received 6 courses of adjuvant chemotherapy with paclitaxel, epirubicin, and carboplatin, and there have been no signs of recurrence for 10 months.